2015
DOI: 10.24059/olj.v20i2.780
|View full text |Cite
|
Sign up to set email alerts
|

Retention, Progression and the Taking of Online Courses

Abstract: Online learning continues to grow at post-secondary institutions across the United States, but many question its efficacy, especially for students most at-risk for failure. This paper engages that issue. It examines recent research on the success of community college students who take online classes and explores similar comparisons using 656,258 student records collected through the Predictive Analytics Reporting (PAR) Framework. In particular, the research investigated retention rates for students in three de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 7 publications
4
78
1
Order By: Relevance
“…The higher rates of transfer and subsequent degree completion are also congruent with recent findings in the California Community College System (Johnson & Cuellar Mejilla, 2014 Of importance also is the finding that participation in online coursework does not contribute significantly to more pronounced dropout trends beyond what is considered typical for community college students. These national level findings do not confirm previous investigations indicating higher levels of dropout among students taking online coursework but does align with more recent research by James, Swan and Daston (2016) indicating no significant differences in retention. Contrary to the conclusion that students who took higher proportions of online courses were slightly less likely to attain a degree or transfer to a four-year college than those who took fewer online courses (Jaggars, 2012) we found that online course-taking is associated with higher and faster degree completion and no significant differences in dropout or transfer.…”
Section: Discussioncontrasting
confidence: 50%
“…The higher rates of transfer and subsequent degree completion are also congruent with recent findings in the California Community College System (Johnson & Cuellar Mejilla, 2014 Of importance also is the finding that participation in online coursework does not contribute significantly to more pronounced dropout trends beyond what is considered typical for community college students. These national level findings do not confirm previous investigations indicating higher levels of dropout among students taking online coursework but does align with more recent research by James, Swan and Daston (2016) indicating no significant differences in retention. Contrary to the conclusion that students who took higher proportions of online courses were slightly less likely to attain a degree or transfer to a four-year college than those who took fewer online courses (Jaggars, 2012) we found that online course-taking is associated with higher and faster degree completion and no significant differences in dropout or transfer.…”
Section: Discussioncontrasting
confidence: 50%
“…Table 1 below provides a brief summary of large-scale studies conducted from 2010 to 2018, providing the institution level at which they were conducted and the primary findings related to course completion and retention/degree completion as appropriate. (2015) Community college Pass rates in online courses lower than traditional on campus Shea & Bidjerano (2016) Community college Significantly more students engaged in online attained a degree than those who did not; women students graduate more quickly when taking online James, Swan, & Daston (2016)…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In a recent special issue of Online Learning that focused on learning analytics, James, Swan, and Daston (2016) examined variables related to retention in students taking only face-toface courses, students taking only online courses, and students taking both face-to-face and online courses. While their primary purpose was to compare students in these three groups, they also provided data concerning retention rates for students enrolled in different types of institutions with different demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%